A new species of Heleobia (Caenogastropoda: Cochliopidae) from the Chilean Altiplano - Collado, Gonzalo A.; Valladares, Moisés A.; Méndez, Marco A. (Zootaxa, 2016)
Cochliopidae Tryon, 1866 is a diverse family of caenogastropods that lives in a wide variety of aquatic habitats primarily in the New World (Hershler &Thompson 1992). In Chile, the species of the group have been traditionally assigned to the genus Littoridina Souleyet, 1852 using conchological characters (Biese 1944, 1947; Stuardo, 1961; Valdovinos 2006) but according to anatomical studies and phylogenetic analysis the majority of them have been reassigned to the genus Heleobia Stimpson, 1865 (Hershler & Thompson 1992; Collado et al. 2011a; Kroll et al. 2012; Collado et al. 2013; Collado et al. 2016). Here we formally describe a new species of the genus Heleobia from Spring 1 in the Carcote saltpan, Chilean Altiplano, based on molecular and morphological characters. Snails from this locality were previously shown to be distinct based on DNA sequences (Collado et al. 2013; Collado et al. 2016).